Political propaganda of the radical Islamic organizations in the USA - I. A. Istomin (Vestnik MGIMO-Universiteta)
Strategy of radical Islamist groups devotes increasing attention to the recruitment of supporters in the U.S. Attraction of the American citizens represents essential component in adaptation of these organizations to the mounting external pressure and contributes to the fulfilling of a set of various objectives. Recent record confirms emergence of the institutionalized system serving the outreach activities of the radical Islamists both on global and local levels. Participation of American citizens in dissemination of Jihadist publications and funding of illegal organizations as well as involvement in terrorist acts proves practical effect of these activities.